ANALISIS KUALITAS BOBA (TAPIOCA PEARL) DAUN KATUK (Sauropus Androgynus) DAN KACANG HIJAU (Vigna Radiata l.) SEBAGAI ALTERNATIF SELINGAN KAYA PROTEIN DAN ZAT BESI BAGI REMAJA ANEMIA - Alifia Citra Ayu Utari; Yenny Moviana; Judiono Judiono; Widi Hastuti; Roro Nur Fauziyyah; Gurid Pramintarto Eko Mulyo (Jurnal Gizi dan Dietetik, 2023)
Anemia can be said to be one of the health problems faced by many Indonesian teenagers, based on the 2018 RISKESDAS data, it can be seen that there is a trend of increasing prevalence of anemic teenagers, namely there are 32% of teenagers in Indonesia who experience anemia. One form of anemia prevention is to increase the intake of foods high in iron and increase the nutritional content of food products. Katuk leaves contain 6,4 g protein and 3,5 mg iron and green beans contain 22,9 g protein and 7,5 iron. Katuk leaves and mung beans can be processed into boba. This study aims to determine the organoleptic quality (color, aroma, taste, texture and overall), protein and iron content of katuk leaf and mung beans boba. The design of this study is experimental. The analyzed quality of boba was organoleptic, protein and iron content. The organoleptic tests were carried out on three balances of katuk leaves and green beans using hedonic tests, namely F1 (70%:30%), F2 (50%:50%) and F3 (30%:70%). Organoleptic test results conducted by 30 quitewell-trained panelists showed the best formula of organoleptic was F1. In 100 gr of boba katuk leaves dan mug beans content 1,65% protein and 1,36 iron. Boba katuk leaves and mung beans can be used as alternative snacks for anemic teenagers.